Association of Maternal Anemia and Risk of Preterm Birth in Pregnant Women at Dr Ruth KM Pfau Civil Hospital Karachi - Batool, Misbah; Habib, Aneela; Bushra; Kumari, Devia; Usman, Marium; Rana, Faiza (Indus Journal of Bioscience Research, 2025)
Background: Anemia is a major public health problem in low- and middle-income countries, including pregnant women. It is linked to poor maternal and infant health outcomes, including preterm birth - a major cause of perinatal morbidity and death. But the link between maternal anemia and preterm birth is conflicting in various populations. Objective: To determine the association between maternal anemia and the risk of preterm birth in pregnant women. Methods: This prospective cohort study was conducted at the Department of Obstetrics and Gynaecology, Dr. Ruth K. M. Pfau Civil Hospital, Karachi from March 2025 to June 2025. A convenience sample of 94 pregnant women were recruited and assigned into anemic (n=47) and non-anemic (n=47) groups. Anemia was defined as hemoglobin levels <11 g/dL in first and third trimesters and <10.5 g/dL in the second trimester. The women were monitored until they gave birth, and preterm birth (<37 weeks) was recorded. SPSS 21 was used to perform the analyses. Chi-square test, relative risk (RR) with 95% confidence interval were computed. P-value ≤0.05 was statistically significant. Results: The mean maternal age was 28.4 ± 5.3 years. Preterm birth occurred in 42.6% of participants. A significantly higher proportion of preterm births was observed in the anemic group (55.3%) compared to the non-anemic group (29.8%) (p = 0.012). The relative risk was 1.86 (95% CI: 1.12–3.08). Stratified analysis showed increased risk in the presence of hypertension, urinary tract infection, iron deficiency, and previous preterm labor. Conclusion: Maternal anemia is significantly associated with an increased risk of preterm birth. Early screening and appropriate management of anemia during pregnancy may help reduce adverse outcomes.